SCIENTOMETRIC PORTRAIT OF NOBEL LAUREATE PIERRE-GILLES DE GENNES - Kalyane, V. L.; Sen, B. K.; Kalyane, V. L.; Sen, B. K. (Malaysian Journal of Library and Information Science, 2017)
Kalyane, V. L., & Sen, B. K. (1996). Scientometric Portrait of Nobel Laureate Pierre-Gilles de Gennes. Malaysian Journal of Library & Information Science, Vol.1, no. 2: 13-26 Presents an analysis of 422 papers by the Nobel laureate Pierre-Gilles de Gennes, a French physicist, published during 1956 to 1995 in diverse fields of science such as, magnetism, superconductors, hydrodynamics, polymers, liquid crystals, gels, and glues. The productivity of the scientist peaked in his 40’s and his journal preference shows a distinct national bias. Despite the scientist’s working with a very large number of collaborators, the percentage of collaborative papers seems to be low i.e. 36%. The receiving of honours and awards seems to attract more collaborators and hike the productivity rate. The scattering of papers over 146 journals does not follow Bradford’s law.